(untitled) (Global Journal of Human-Social Science, 2017)
Two parallel articulated discourses on internationalization, and on higher education are currently involved in a dynamic process. The factors that shape this dimension of internationalizing education in higher education have got its inspiration from the evolving concept, ‗Globalization’ particularly. This essay, however, aims at exploring those dimensions in terms of the rise of new economic powers; regional state alliances; multi-cultural tastes in a given environment; and the accelerating use of academic, and non academic information through accessing more advanced communication technologies. Higher education, as the essay progresses, states that it makes a bridge between a particular entity, and global knowledge sphere. The context of higher education particularizes globalization as being the most important factor that observes challenges and success being greatly visible among many nations.